Well‐Defined Poly(Ester Amide)‐Based Homo‐ and Block Copolymers by One‐Pot Organocatalytic Anionic Ring‐Opening Copolymerization of N‐Sulfonyl Aziridines and Cyclic Anhydrides - Xu, Jiaxi; Hadjichristidis, Nikos (Angewandte Chemie International Edition, 2021)
We report a new synthetic methodology for poly(ester amide)s by anionic ring‐opening copolymerization of N‐sulfonyl aziridines and cyclic anhydrides. Phosphazenes organocatalysts have been found to promote a highly‐active, controlled, and selective alternating copolymerization in the absence of any competitive side reaction (zwitterionic mechanism and exchange transacylations). Mechanistic studies have shown first‐order dependence of the copolymerization rate in N‐sulfonyl aziridines and phosphazenes, and zero‐order in cyclic anhydrides. This one‐pot methodology leads not only to homopolymers but also to poly(ester amide)‐based block copolymers. Two catalytic cycles involving ring‐opening alternating copolymerization of N‐sulfonyl aziridines with cyclic anhydrides and ring‐opening polymerization of N‐sulfonyl aziridines have been proposed to explain the one pot synthesis of poly(ester amide)‐based homo‐ and block copolymers. Phosphazene organocatalysts have been found to promote a highly‐active, controlled, and selective alternating ring‐opening copolymerization of N‐sulfonyl aziridines and cyclic anhydrides. This one‐pot methodology leads not only to homopolymers but also to poly(ester amide)‐based block copolymers.